Performance Pay and Risk Aversion - Christian Grund; Dirk Sliwka (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
A main prediction of agency theory is the well known risk-incentive trade-off. Incentive contracts should be found in environments with little uncertainty and for agents with low degrees of risk aversion. There is an ongoing debate in the literature about the first trade-off. Due to lack of data, there has so far been hardly any empirical evidence about the second. Making use of a unique representative data set, we find clear evidence that risk aversion has a highly significant and substantial negative impact on the probability that an employee's pay is performance contingent.
urn:nbn:de:bvb:19-epub-13450-8
Keywords: J33; M52; D80; 330; Agency theory; GSOEP; Incentives; Pay for performance; Performance appraisal; Risk; Risk aversion